Agricultural machinery service adoption and farmland transfer-in decision: evidence from rural China - Zhang, Yujiao; Zhang, Jian; Liu, Yang; Zhu, Peixin (Frontiers in Environmental Science, 2023)
With the deepening of China’s agricultural labor division, the rapid development of agricultural machinery service has had a profound impact on farmland scale management. Based on the new classical economic and transaction cost theories, this paper investigates the impact mechanism of agricultural machinery service on farmers’ farmland transfer-in decision from the dual perspectives of transaction cost and benefit of labor division, and uses the national rural survey data of the Chinese Family Database to conduct empirical research by using ordinary least squares (OLS) model and limited information maximum likelihood method (LIML). The study finds that, first, agricultural machinery service expands farmers’ farmland transfer-in decision by encouraging them to obtain the economic efficiency of labor division. Not only agricultural machinery service can alleviate the constraint of farmers’ farmland transfer in labor and capital, but also reduce the service transaction cost and increase farmers’ share of the division of labor economy, which further stimulates farmers to expand the scale of management. Second, with the deepening of labor division of agricultural machinery services, the higher transaction efficiency of agricultural machinery service promotes farmers’ farmland transfer-in participation. As long as the marginal net benefit obtained is greater than zero, farmers have incentives to expand the scale of farmland. Therefore, in order to promote China’s farmland scale management, the professional, whole-process and large-scale development of agricultural machinery services should be further promoted, and the service capacity and fields should be expanded, so that outsourcing services can be better provided to agricultural production demanders. At the same time, the technical standards, supervision system, and service platform of agricultural machinery should be established and improved, so as to enhance the bargaining position of farmers in service outsourcing transactions, thus promoting the development of agricultural division of labor to a higher level, and realizing the mutual promotion and mutual benefit of agricultural machinery service subjects and agricultural land scale management subjects.